2018
DOI: 10.1111/tmi.13175
|View full text |Cite
|
Sign up to set email alerts
|

Removal of user fees and system strengthening improves access to maternity care, reducing neonatal mortality in a district hospital in Lesotho

Abstract: Objective Lesotho has one of the highest maternal mortality rates in the world. While at primary health care (PHC) level maternity care is free, at hospital level co‐payments are required from patients. We describe service utilisation and delivery outcomes before and after removal of user fees and quality of delivery care, and associated costs, at St Joseph's Hospital (SJH) in Roma, Lesotho. Methods We compared utilisation of delivery services, stillbirths and maternal and neonatal mortality for the periods be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this perspective, fees of 12-30 USD are considerable and a great burden to the family economy. Previous studies from various sub-Saharan countries could show that the removal of delivery fees resulted in an increase of facility-based deliveries, and a study from Lesotho showed that the removal of ambulance and delivery fees resulted as well in a decrease in neonatal and maternal mortality rates (16)(17)(18)(19)(20). The ndings of this study implicate that an excess of about 80 CSs per 1000 births as a consequence of user fees might have been avoided by more timely birth attendance.…”
Section: Discussionmentioning
confidence: 53%
“…In this perspective, fees of 12-30 USD are considerable and a great burden to the family economy. Previous studies from various sub-Saharan countries could show that the removal of delivery fees resulted in an increase of facility-based deliveries, and a study from Lesotho showed that the removal of ambulance and delivery fees resulted as well in a decrease in neonatal and maternal mortality rates (16)(17)(18)(19)(20). The ndings of this study implicate that an excess of about 80 CSs per 1000 births as a consequence of user fees might have been avoided by more timely birth attendance.…”
Section: Discussionmentioning
confidence: 53%
“…This is in line with a finding from Lesotho which reported that pregnancy-related complications doubled the MHSU in higher hospitals. 26 Women with identified and known complications related to their pregnancy might have good health-seeking behavior to mitigate risk. Similarly, the odds of adherence to MHSU were higher among women having primary/secondary and above educational background than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, fees of 12–30 USD are considerable and a great burden to the family economy. Previous studies from various sub-Saharan countries could show that the removal of delivery fees resulted in an increase of facility-based deliveries, and a study from Lesotho showed that the removal of ambulance and delivery fees resulted as well in a decrease in neonatal and maternal mortality rates [ 16 20 ]. The findings of this study implicate that an excess of about 80 CSs per 1000 births as a consequence of user fees might have been avoided by more timely birth attendance.…”
Section: Discussionmentioning
confidence: 99%